Causal association analysis between blood metabolomes and osteopenia and therapeutic target prediction for mechanomedicine - Ruobing Liu; Yaru Huang; Maogang Jiang; Fei Xu; Qilin Pei; Jiajun Ma; Youru Li; Siqi Shen; Bo Zhang; Xiangyang Guo; Jing Cai; Wenwen Wang (Mechanobiology in Medicine)
Blood metabolomes have been linked to osteoporosis, yet the precise causal relationship with osteopenia, its preventable early stage, remains unclear. This study aimed to uncover the genetic causality between blood metabolomes and osteopenia, pinpointing potential targets for mechanomedicine. Utilizing genome-wide association study summary statistics, we analyzed 1091 metabolites and 309 metabolite ratios from 8299 individuals, correlating them with total body bone mineral density (BMD) from 56,284 individuals in the IEU GWAS database and osteopenia data from 408,961 European populations. Through two-sample Mendelian randomization, we investigated the association between blood metabolomes and skeletal characteristics. We then conducted summary-data-based Mendelian randomization (MR) analysis and colocalization analyses to identify causal genes related to skeletal phenotypes, predicting therapeutic targets for osteopenia. Expression of potential targets in osteocytes under fluid shear stress (FSS) stimulation was tested using qRT-PCR to explore mechanical sensitivity and bone health mechanisms. Our findings revealed five metabolites affecting total body BMD and osteopenia, with biliverdin emerging as a potential protective factor against osteopenia (OR ​= ​0.93, 95 ​%CI ​= ​0.88–0.98, P ​= ​0.009). Additionally, three genes—LRRC14, SLC22A16, and TNFRSF1A—were identified as potential therapeutic targets for osteopenia. Notably, LRRC14 and TNFRSF1A are also associated with other musculoskeletal diseases. In vitro experiments showed that FSS significantly increased LRRC14 expression in osteocytes, suggesting its potential as a mechanosensitive factor. This study identifies candidate blood metabolites and mechanomedicine targets for osteopenia, offering a scientific basis for new diagnostic and treatment strategies and deepening our understanding of bone mechanics response characteristics.